Muscle-bone interactions: From experimental models to the clinic? A critical update. (5th September 2016) - Laurent, Michaël R.; Dubois, Vanessa; Claessens, Frank; Verschueren, Sabine M.P.; Vanderschueren, Dirk; Gielen, Evelien; Jardí, Ferran
Abstract: Bone is a biomechanical tissue shaped by forces from muscles and gravitation. Simultaneous bone and muscle decay and dysfunction (osteosarcopenia or sarco-osteoporosis) is seen in ageing, numerous clinical situations including after stroke or paralysis, in neuromuscular dystrophies, glucocorticoid excess, or in association with vitamin D, growth hormone/insulin like growth factor or sex steroid deficiency, as well as in spaceflight. Physical exercise may be beneficial in these situations, but further work is still needed to translate acceptable and effective biomechanical interventions like vibration therapy from animal models to humans. Novel antiresorptive and anabolic therapies are emerging for osteoporosis as well as drugs for sarcopenia, cancer cachexia or muscle wasting disorders, including antibodies against myostatin or activin receptor type IIA and IIB (e.g. bimagrumab). Ideally, increasing muscle mass would increase muscle strength and restore bone loss from disuse. However, the classical view that muscle is unidirectionally dominant over bone via mechanical loading is overly simplistic. Indeed, recent studies indicate a role for neuronal regulation of not only muscle but also bone metabolism, bone signaling pathways like receptor activator of nuclear factor kappa-B ligand (RANKL) implicated in muscle biology, myokines affecting bone and possible bone-to-muscle communication. Moreover, pharmacological strategies inducing isolated myocyte hypertrophy may not translate into increased muscle power because tendons, connective tissue, neurons and energy metabolism need to adapt as well. We aim here to critically review key musculoskeletal molecular pathways involved in mechanoregulation and their effect on the bone-muscle unit as a whole, as well as preclinical and emerging clinical evidence regarding the effects of sarcopenia therapies on osteoporosis and vice versa. Highlights: Simultaneous bone and muscle decay and dysfunction are seen in aging and disuse. Mechanical, endocrine, nutritional and neural signals co-regulate bone and muscle. Muscle-bone interactions further involve local growth factors and myokines. Myostatin and activin receptor inhibition holds promise for sarco-osteoporosis. We recommend an integrated view on the bone-muscle unit.